ChemInform Abstract: Three‐Component, One‐Pot Sequential Synthesis of Functionalized Cyclazines: 3H‐1, 2a1, 3‐Triazaacenaphthylenes. Issue 23 (16th May 2013) - Shen, Jingkang; et al., et al.
Abstract An efficient and widely applicable method to prepare new triazaacenaphthylenes as well as tetraazaacenaphthylenes is reported.